2018
DOI: 10.1002/jbm.b.34077
|View full text |Cite
|
Sign up to set email alerts
|

The effects of bi‐functional anti‐adhesion scaffolds on flexor tendon healing in a rabbit model

Abstract: Progressive tendon adhesion is a major challenge in flexor tendon repair. The authors developed a bifunctional anti-adhesion scaffold and hypothesized that its application would reduce adhesion formation and deliver mesenchymal stem cells (MSCs) to enhance tendon healing. The scaffold was fabricated by an electrospinning machine before surface modification. The flexor tendons of 29 New Zealand rabbits underwent surgical repair and randomized to control, scaffold and scaffold loaded with MSC group. At 3 and 8 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…(3) More deliberation needs to be given to the microstructure of the material. For example, the thickness, pore diameter and porosity of the membrane affects the space of the tendon sheath, tendon slipping ability, infiltration of cells and various functional molecules as the result of a bi-functional anti-adhesion scaffold studied by Liao et al [34] (4) Lack of clinical practices. It should be remembered that in animal experiments, there are aspects different from humans [11], including anatomical characteristics, healing potentials, and resistance to infection, tolerance of foreign matter or immune responses, as well as compliance in the process of treatment, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(3) More deliberation needs to be given to the microstructure of the material. For example, the thickness, pore diameter and porosity of the membrane affects the space of the tendon sheath, tendon slipping ability, infiltration of cells and various functional molecules as the result of a bi-functional anti-adhesion scaffold studied by Liao et al [34] (4) Lack of clinical practices. It should be remembered that in animal experiments, there are aspects different from humans [11], including anatomical characteristics, healing potentials, and resistance to infection, tolerance of foreign matter or immune responses, as well as compliance in the process of treatment, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that without affecting the range of motion of the healed joint, hydrogels can be used as a scaffold for tendon cell extension in the process of tendon repair with a certain degree of toughness to protect the tendon from rerupturing and provide a proper molding time to ensure that it can wrap around the repaired parts better. Besides, as a solution, hydrogels type barriers are easier to apply but may be washed out readily and render lower efficacy [34].…”
Section: Hydrogels Cross-linked With Functional Moleculesmentioning
confidence: 99%
“…[ 2 ] In order to design a proper scaffold for tendon and ligament engineering, various natural materials, biodegradable polymers, and composite biomaterials have been considered. [ 67–76 ] Commercial materials used to produce and fabricate scaffolds for this application include synthetic degradable, synthetic nondegradable, biological, and naturally derived materials. [ 2 ] Synthetic biomaterials have the great advantage of improving tissue repair by sharing mechanical loads with the host tissue.…”
Section: Tendon and Ligament Tissue Engineeringmentioning
confidence: 99%
“…The architecture and structure of electrospun scaffolds allow the incorporation of natural components into the synthetic system to improve its biological responses and tissue healing. [ 71,72 ] In order to enhance the biocompatibility of synthetic scaffolds, the components of the ECM, e.g., collagen, can be added. [ 68,180 ] Even though collagen has high biocompatibility, its low mechanical properties have suggested that it should be combined with synthetic polymers, which have superior mechanical behavior.…”
Section: Fiber‐based Engineered Scaffolds For Tendons and Ligamentsmentioning
confidence: 99%
“…Many methods have been used to prevent tendon adhesion, such as the improvement of surgical technology, the use of barriers, systemic or local application of drugs and chemicals. Although these methods can reduce adhesions to some extent, the residual or recurrent adhesions still need to be resolved [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%